Tarikh tasyri’ di beberapa negara islam dan faktor sosio-kultural yang memengaruhinya - Jannah, Khurfatul (Maliki Interdisciplinary Journal, 2026)
The History of Tasyri' in Several Islamic Countries and the Socio-Cultural Factors that Influence It discusses the historical evolution of Islamic law legislation in Saudi Arabia, Egypt, Indonesia, and Pakistan. This paper outlines the diverse patterns of Islamic law implementation, influenced by dominant schools of thought such as the conservative Hanbali in Saudi Arabia, the reformist Shafi'i-Hanafi in Egypt, the contextual Shafi'i in Indonesia through the KHI, and the Islamized Hanafi in Pakistan. The main socio-cultural factors include politics (monarchy vs. democracy), socio-culture (customs based on sharia), economics, education, and globalization, which shape the adaptive dynamics of Islamic law. The study of Tarikh Tasyri' between countries emphasizes the flexibility of Sharia, the plurality of its application, and its benefits for the development of moderate and relevant law in the modern era, supporting contextual ijtihad for social justice. The conclusion affirms Islamic law as a dynamic system that is responsive to changing times without sacrificing basic principles.